The Physical Vulnerability to Climate Change Index computed at the sub-national level - Goujon, Michaël; Santoni, Olivier; Wagner, Laurent (HAL CCSD, 2022)
The Physical Vulnerability to Climate Change Index (Feindouno et al., 2020) is a composite indicator computed at country level (191 countries) that can be used for the identification of the most vulnerable countries and as a criterion for guiding the international allocation of resources for adaptation. In this paper we present the details of the computation of the PVCCI at the sub-national level (2nd sub-national administrative level in the GADM database), representing 47,138 administrative units in the World (covering all land but Antarctica). It aims at measuring vulnerability to climate change at a finer geographic level, which is particularly relevant for countries that are characterized by high geoclimatic diversity. It would help identify the most vulnerable subnational administrative units and could be used as an instrument of adaptation planning.